Determinant of Optimal Adherence to Antiretroviral Drugs Among HIV Positive Clients in Federal Capital Territory of Nigeria - Oluwasina, Folajinmi; Olalekan, Adebimpe; Onifade, Bodunde; Obi, Daniel Ebenezer; Kolawole, Mobolaji (International Journal For Research In Health Sciences And Nursing, 2019)
Medication adherence is an important component in the care of People Living with HIV (PLHIV). The modification to combination therapies for treating Human Immunodeficiency Virus (HIV)-infected individuals has increased adherence challenges for both patients and health-care providers. Factors associated with non-adherence appears to be patient-related. This article aims to examine the pattern and determinants of optimal adherence to antiretroviral therapy among people living with HIV. A descriptive, cross sectional study using a systematic sampling technique to select 760 persons living with HIV in Federal Capital Territory (FCT) ART clinics, Nigeria. (54%) were Females while 46% were males. 87% of respondents have been on ARV regimen in the last 3 years. About 91% had good knowledge of medication adherence 8% do not understand what adherence to medication means .Most (79%) of HIV patient’s adequate adherence to ART while others (13%) usually had stopped taking their medication when they feel better about their health. The commonest source of information about medication adherence to ARV was through the adherence counselor at during ART clinics (77%). Sixty percent of the respondents agreed that adherence to ARV medication helps in improving standard of living Factors that hindered effective adherence to treatment included poor providers’ attitude (33.3%) and forgetfulness to take their medication and pill burden (25%). Respondents who did not adhere to treatment were less likely to subsequently adhere to ARV medication (OR= 0.324, 95%CI= 0.1-0.5). Use of treatment partner or reminders was the major determinant of medication adherence (OR = 3.4, 95%CI = 1.3-8.7). Majority of the respondents are knowledgeable about medication adherence.